2010
DOI: 10.1002/ajmg.a.33801
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 21q22.11‐q22.13 presenting as a Fanconi anemia phenotype

Abstract: We report on a 5-year-old Caucasian female with multiple anomalies whose deletion, 46,XX,del(21)(q22.11q22.13), was determined by a 105K oligonucleotide-based microarray. This case is a unique deletion that mimicked Fanconi anemia (combination of thrombocytopenia, thumb anomalies, congenital heart defects, borderline small head circumference, strabismus, hydronephrosis, and significant developmental delay) but testing for Fanconi anemia was negative, as was testing for a wide array of genetic/metabolic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…With the availability of CMA analysis, more patients with subtle 21q deletions have been described, and a syndromic form of intellectual disability, growth delay, and thrombocytopenia has recently been described in subjects with a critical deletion interval spanning 21q22.11q22.12 including the RUNX1 gene [Hoyer et al, 2007;Beri-Dexheimer et al, 2008;Shinawi et al, 2008;Lyle et al, 2009;Katzaki et al, 2010;van der Crabben et al, 2010;Byrd et al, 2011;Thevenon et al, 2011]. Our patient appears to fit this phenotype and shares the findings of low birth weight, short stature, and microcephaly identified in several subjects.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…With the availability of CMA analysis, more patients with subtle 21q deletions have been described, and a syndromic form of intellectual disability, growth delay, and thrombocytopenia has recently been described in subjects with a critical deletion interval spanning 21q22.11q22.12 including the RUNX1 gene [Hoyer et al, 2007;Beri-Dexheimer et al, 2008;Shinawi et al, 2008;Lyle et al, 2009;Katzaki et al, 2010;van der Crabben et al, 2010;Byrd et al, 2011;Thevenon et al, 2011]. Our patient appears to fit this phenotype and shares the findings of low birth weight, short stature, and microcephaly identified in several subjects.…”
Section: Discussionsupporting
confidence: 73%
“…At least one report has implicated deletion of the ITSN1 gene as critical for the association with intellectual impairment [Beri-Dexheimer et al, 2008], and others have implicated DSCR1 (RCAN1), and CLIC6 [Shinawi et al, 2008], but deletion of genes such as OLIG1 and OLIG2 may also be important contributors to the cognitive phenotype [Pritchard et al, 2008], as recent studies suggest that dosage of these genes is critical and their triplication may account for the neurological phenotype in murine models of Down syndrome [Chakrabarti et al, 2010]. Of note, cardiac malformations have been described in a subset of patients with 21q22 deletions encompassing RUNX1, including one with tetalogy of Fallot [Lindstrand et al, 2010] like our patient, one with transposition of the great vessels [Shinawi et al, 2008], four with an atrial septal defect [Beri-Dexheimer et al, 2008;Katzaki et al, 2010;Byrd et al, 2011;Thevenon et al, 2011], and three with unclassified heart defects [Yao et al, 2006;Lyle et al, 2009]. Several subjects have demonstrated corpus callosum dysgenesis (not apparent in our patient), which in combination with thrombocytopenia, intellectual disability, and dysmorphic features, has been termed the Braddock-Carey syndrome [Braddock and Carey, 1994;Thevenon et al, 2011].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34][35][36] All but one case 32 reported thrombocytopenia, with qualitative platelet defects described in 2 cases. 30,36 MDS/AML developed in 3 cases, with a median age of onset of six years (range 5-8 years). This median age is much lower than that of traditional FPD/AML and suggests that other genes within the 21q22 locus may also be important in leukemogenesis.…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…This gene encodes a cell adhesion molecule and is expressed in the heart during cardiac development and was proposed as a candidate gene for Down syndrome and congenital heart disease (DS-CHD) [27]. Congenital heart defect in the form of (VSD) was observed in our patient, and in other reported cases, however they reported deleted segment in more proximal region between (30,02-37,55Mb) [12,28] and (34,796 and 35,363) [9] including genes CLIC6 and RUNX1. Lindstrand [9] suggested that a critical region of 0.5 Mb between 34,796 and 35,363 including CLIC6 and RUNX1 and another 2 genes is associated with congenital heart disease, however, this region has shown duplication in our patient which might indicate different mechanism in causing heart defect.…”
Section: Discussionmentioning
confidence: 51%